Availability Prediction Methods for Terrestrial Free-Space-Optical Link Under Tropical Climate - Ahmed Basahel; Md Rafiqul Islam; Mohamed Habaebi; Suriza Ahmad (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Free-space optical (FSO) links provide high speed point-to-point wireless communication, but its availability can easily be affected by weather conditions. In heavy rainfall regions, FSO links are relatively sensitive to rain. Availability prediction of FSO is indispensable part, especially in tropical areas. In this paper, methods to predict FSO link availability are presented. The overall performance of FSO link is described in terms of the availability that can be achieved over anticipated link distance. The availability prediction methods demonstrated for an FSO link ranges up to 5 km. The availability prediction methods are based on long-term statistics of atmospheric attenuations and FSO link budget under tropical climate condition. In tropical regions, for a terrestrial FSO link, carrier class availability can be achieved over a few hundred meters only; whereas enterprise class availability can be achieved over a few kilometers link distances.